Application of enhanced recovery after surgery during the perioperative period in children with Meckel’s diverticulum–a single-center prospective clinical trial - Wang, Cuicui; Wang, Youliang; Zhao, Ping; Li, Ting; Li, Fan; Li, Zhi; Qi, Yingwen; Wang, Xuewu; Shi, Weidong; Liu, Lina; Li, Gamei; Wang, Yong (Frontiers in Pediatrics, 2024)
Background: Enhanced recovery after surgery (ERAS) has been widely used in adult surgery. However, few studies have reported the efficacy of ERAS in paediatric patients with Meckel's diverticulum (MD), the aim of the study was to prospectively evaluate the safety and efficacy of ERAS in treating MD. Methods: A prospective randomised controlled study of children with MD admitted to our hospital from Jan 1, 2021 to Dec 31, 2023 were conducted, we developed and implemented an ERAS program for this patients. All cases were strictly selected according to the inclusion and exclusion criteria. Among these patients, they were randomly assigned to the ERAS group or the traditional (TRAD) group with random number table row randomization. The main observational indicators were operation time, intraoperative hemorrhage, FLACC pain scale results on 2h, 6h, 12h, 24h after surgery, length of postoperative stay (LOPS), time to first defecation, time to first eating after surgery, time to discontinuation of intravenous infusion, total treatment cost, incidence of postoperative complications, 30-day readmission rate and parental satisfaction rate. Results: A total of 50 patients underwent Meckel's diverticulectomy during this period, 7 patients were excluded, 23 patients were assigned to the ERAS group and 20 patients were assigned to the TRAD group. There were no significant differences in demographic data and operation time, intraoperative hemorrhage. The FLACC pain scale results on 2h, 6h, 12h, 24h after surgery were significantly lower in the ERAS group. The LOPS was 6.17 ± 0.89 days in the ERAS group and 8.30 ± 1.26 days in the TRAD group, resulting in a significantly shorter LOPS in ERAS group. ERAS could also reduce the first postoperative defecation time, the time to first eating after surgery and the time to discontinuation of intravenous infusion. The treatment cost was decreased in the ERAS group. The rate of complications and 30-day readmission were not significantly different between the two groups. Conclusions: In this single-center study, the ERAS protocol for patients with MD requiring surgery was safe and effective.